Examining the Disaster Awareness Levels of Secondary School Students - Durmuş, Esen; Kınacı, Müşerref Kübra; Kuruyer, Dılan (My University, 2024)
Natural events are considered disasters when they cause harm to people and living spaces. Since natural disasters cannot be prevented, individuals need to learn to live with and become aware of them. This awareness is critical in minimizing the impact of disasters and can only be achieved through disaster education. Disaster-related outcomes in secondary school are concentrated in the social studies curriculum, and therefore, social studies is an important subject for disaster education. If high-quality disaster education is provided as a part of this course, students are likely to acquire skills to cope with disasters. In this regard, the purpose of this study was to examine the level of disaster awareness among secondary school students. Accordingly, a mixed-method approach, combining qualitative and quantitative methods, was employed in the study. This study was conducted using an explanatory sequential design within the mixed-method approach. The sample was selected using criterion sampling, one of the purposeful sampling methods. Consequently, the study was conducted with 396 students selected from the 5th, 6th, and 7th grades during the 2023-2024 academic year. The study group was selected on a voluntary basis from the sample to which quantitative data were applied. In the quantitative part of the study, the \"Disaster Awareness Scale for Secondary School Students\" was used to collect data, and in the qualitative part, a semi-structured interview form developed by the researchers was used. The quantitative findings of the study showed that secondary school students had high levels of disaster awareness. However, the qualitative findings did not support the quantitative findings.
Keywords: Natural Disasters; Social Studies; Disaster Education; Disaster Awareness